2003
DOI: 10.1111/1540-5826.00068
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Algebra to Students with Learning Difficulties: An Investigation of an Explicit Instruction Model

Abstract: Thirty-four matched pairs of sixth-and seventh-grade students were selected from 358 participants in a comparison of an explicit concreteto-representational-to-abstract (CRA) sequence of instruction with traditional instruction for teaching algebraic transformation equations. Each pair of students had been previously labeled with a specific learning disability or as at risk for difficulties in algebra. Students were matched according to achievement score, age, pretest score, and class performance. The same mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(208 citation statements)
references
References 8 publications
9
190
0
9
Order By: Relevance
“…The result that DCRAI is more effective for teaching geometry and algebra is consistent with the findings (e.g. Witzel et al 2003;Witzel, 2005;Witzel et al 2008;Stricckland & Maccini, 2010) that CRA instructional approach is effective for teaching mathematics at the middle, high, and secondary schools. However, Witzelet al (2008) and Butler et al (2003) indicate that CRA instructional approach is not a simple process to apply by teachers to mathematics content.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The result that DCRAI is more effective for teaching geometry and algebra is consistent with the findings (e.g. Witzel et al 2003;Witzel, 2005;Witzel et al 2008;Stricckland & Maccini, 2010) that CRA instructional approach is effective for teaching mathematics at the middle, high, and secondary schools. However, Witzelet al (2008) and Butler et al (2003) indicate that CRA instructional approach is not a simple process to apply by teachers to mathematics content.…”
Section: Discussionsupporting
confidence: 86%
“…This is reflected in the findings of Delvin (2000) that for students to understand abstract concepts more easily and solve problems in mathematics, it is important for them to learn precursor concepts in a concrete manner first. One way to simplify students' understanding of abstract concepts is to transform such complex concepts into concrete manipulations and pictorial representations (Witzel, 2003).…”
Section: Concrete Representational Abstract Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the arts play critical roles as scaffolds to help students with disabilities to get into an abstract world. STEM disciplines often contain abstract concepts (Brigham, Scruggs, & Mastropieri, 2011) that require understanding of theoretical properties beyond what students can manipulate on a practical level (Witzel, Mercer, & Miller, 2003). Due to the poor cognitive abilities and related skills students with disabilities have been shown to have, it is important to provide scaffolds with student-participation activities that can simplify abstract concepts in order to develop precursor concepts (Devlin, 2000).…”
Section: From Stem To Steam: Adding the Arts To Stem For Students Witmentioning
confidence: 99%
“…For example, Lord (1997) reports on a study in which students in a constructivist biology classroom performed better than students taught by the standard approach. A matched pairs study by Witzel, Mercer and Miller (2003) showed that middle school students introduced to the concept of solving algebraic equations through concrete manipulatives outperformed students who received traditional instruction. A study of constructivist-based learning materials in social studies (Karaduman & Gültekin, 2007) shows that such activities can improve student retention of material.…”
Section: Literature Reviewmentioning
confidence: 99%